2014
DOI: 10.1097/qad.0000000000000125
|View full text |Cite
|
Sign up to set email alerts
|

CRF01_AE subtype is associated with X4 tropism and fast HIV progression in Chinese patients infected through sexual transmission

Abstract: CRF01_AE, a predominant HIV-1 subtype in Chinese HIV-1 sexually infected patients, tends to be associated with fast progression to AIDS and advanced immunodeficiency, which might be ascribed to high proportion of X4 tropism. Further investigation of these risk factors may have significant implications to clinical practice and policy-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 34 publications
10
89
0
Order By: Relevance
“…The subtype distribution in our study was 53.5% CRF01_AE, 14.9% B, 27.2% CRF07_BC/CRF08_BC and 4.4% other subtypes, which was consistent with previous reports 17, 18 , indicating that recombinant forms of the virus might be on the rise worldwide, which have already been associated with faster disease progression as seen in Cuba 19 and Brazil 20 . Most importantly, our study demonstrated that CRF01_AE is associated with faster HIV/AIDS progression, which is in agreement with a previous study conducted in China 14 . In another study, Ng et al .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The subtype distribution in our study was 53.5% CRF01_AE, 14.9% B, 27.2% CRF07_BC/CRF08_BC and 4.4% other subtypes, which was consistent with previous reports 17, 18 , indicating that recombinant forms of the virus might be on the rise worldwide, which have already been associated with faster disease progression as seen in Cuba 19 and Brazil 20 . Most importantly, our study demonstrated that CRF01_AE is associated with faster HIV/AIDS progression, which is in agreement with a previous study conducted in China 14 . In another study, Ng et al .…”
Section: Discussionsupporting
confidence: 93%
“…A systematic review and meta-analysis conducted in China showed that the pooled prevalence of CRF01_AE, subtype B, CRF07_BC, CRF08_BC, and subtype C was 44.54% (95% CI 40.81–48.30), 18.31% (95% CI 14.71–22.17), 16.45% (95% CI 13.82–19.25), 2.55% (95% CI 1.56–3.73), and 0.37% (95% CI 0.11–0.72), respectively 13 . Notably, the median time from the estimated date of seroconversion to the development of AIDS in the Chinese HIV-1 population was shorter compared with that in other countries 14–16 . Thus, understanding the factors that affect HIV/AIDS progression is vitally important for personalized disease management and clinical counselling.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Due to the association between X4/DM viruses and accelerated disease progression, [13,14] patients with X4/DM viruses are at higher risk of faster CD4+ cell count decline and deterioration of immune status in early stage of infection. Recently, a severe loss of CD4+ T cell count among CRF01_AE-infected patients was observed in China, [12,40] which might be ascribed to transmission of X4/DM viruses.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant HIV-1 subtype in our sample set was CRF01_AE, which is mainly transmitted through sexual routes and has the characteristics of faster clinical progression than other subtypes (Li et al 2014). All of these factors support the importance to initiate ART early as a preventative method in Guangxi serodiscordant couples to reduce intra-family sexual transmission.…”
Section: Discussionmentioning
confidence: 99%